Flood Risk Mapping of Kamla River Basin using HEC-RAS 2D Model - Birendra Pandit,; Pawan Bhattarai,; Pawan Bhattarai, (Advances in Engineering and Technology: An International Journal, 2023)
Flood is a natural disaster that occurs repeatedly in Nepal and causes significant losses in terms of life and property particularly in low land areas around the river courses. Kamla basin is highly susceptible to flooding and had experienced many disastrous floods in the past. Flood mitigation measures generally consists of two main methods which are structural and non-structural methods. Nowadays, the importance of using nonstructural method such as flood hazard map and flood risk map are increasing because of environmental and economic aspects. In this study, the assessment of flood hazard and risk was carried out for Kamla River basin. Floods are simulated using the HEC-RAS 2D hydraulic model. The flood hazard map was prepared using the simulation result by classifying into four hazard level, corresponding to different inundation depth. The exposed elements considered for the vulnerability assessments are building, population and agriculture area. Finally, to evaluate the flood risk, a flood risk map of wards under the study area was prepared for 25year,50year and 100-year return period flood events based on the product of flood hazard and vulnerability weightage. The study’s findings may help in the planning and management of Kamla River flood plain region to avoid future likely disasters.